Hubungan Jenis Kelamin Dan Penggunaan Media Sosial Dengan Perilaku Narsistik Remaja - Oca Salsa Kasalina; Nanang Martono; Try Rini Widyastuti (Jurnal Neo Societal, 2024)
This study aims to explain the relationship between sex and social media use on narcissistic behavior of high school adolescents in Banyumas. The study used a survey method conducted at SMAN 1 Ajibarang, Banyumas, Central Java. The total population of the school is 1,217 students. The sample is taken using a simple random sample method; The number of samples is determined by the Slovin formula, so the number of samples is 302 students. The results of this study showed that based on the Chi-Squared test with a significance level (0.05) showed a result of 0.437; This means that p (0.437) > sig (0.05). Thus, it can be concluded that gender is not the main factor influencing narcissistic behavior. The second result showed that based on the Tau Kendall Correlation Test showed a positive relationship between the intensity of social media use and adolescent narcissistic behavior (p = 0.00 < 0.05). That is, the higher the intensity of adolescents in using social media, the tendency to behave narcissistically also increases. Proper education about the risks and benefits of social media use can also help teens develop healthy use skills and positive behaviors online.